A Brief Review on Synthesis of Metal Oxide Based Nano-composites and their Photocatalytic Applications - Sasikanth, S. M.; .R, Ganapathi Raman (International Journal of Advanced Science and Technology, 2019)
Nanocomposite, a multiphase solid material which is having the phases of one, two, or three dimensions less than 100 nanometers. These materials have the physical and chemical properties which depend on the morphology and the interfacial characteristics of the component materials. Metal oxide nanocomposites have proven themselves their importance in the present time with a wide variety of applications in every industrial sector. Wet chemical methods are one of the simplest routes for the synthesis of the metal oxide nanocomposites, and they are cost effective as well. For the synthesis of the complex matrix-based metal oxide nanocomposites, Co-precipitation is the method used. The simple synthesis methods make them unique material for different applications. This review paper discusses the synthesisof metal oxide nanocomposites and their applications.